Hydroa vacciniforme. Case report. - Banerjee, J.; Chow, N.; Ghorbanian, S.; Rahman, M.M. (European Journal of Pediatric Dermatology, 2009)
Vesicular rash in children is commonly caused by various viruses or bacterial infections. It could be a result of some form of photodermatosis or autoimmune diseases as well. Hydroa vacciniforme (HV) is a rare form of idiopathic photodermatosis with an onset in childhood, characterized by acute vesiculation, crusting and scarring following exposure to sun.